Paying for avoided deforestation in the Brazilian Amazon: from cost assessment to scheme design - Borner, J.; Wunder, Sven (2008)
Reducing emissions from deforestation and degradation (REDD) is considered a signifi cant mitigation opportunity. Forest loss in the Brazilian Amazon has traditionally been highest in the world and, thus, represents a likely target for future REDD initiatives. The paper presents an ex-ante assessment of the potential REDD costs in two of the three largest states in the Brazilian Amazon using offi cial land use and cover change statistics. The two states, Mato Grosso and Amazonas, historically feature largely different land use dynamics. The findings focus on the opportunity costs of REDD and suggest that at least 1 million ha of projected deforestation in Mato Grosso and Amazonas could be compensated for at current carbon prices until 2017. Total costs may differ between US$ 330 million and over US$ 1 billion depending on how payment mechanisms are designed. Implications of payment scheme design for the political economy of REDD are discussed